Agroclimatic effects on milk production and sub-clinical mastitis prevalence in dairy cattle - Susanty, H.; Purwanto, B.P.; Sudarwanto, M.; Atabany, A. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The present study was done to observe effect of agroclimate on milk production and prevalence of sub-clinical mastitis of local Holstein-Friesian dairy cattle in Indonesian small holder dairy farms. The research side were located in Region of <1000 masl and ≥1000 m above sea level (asl) in west Java. Data were obtained from 133 small holder dairy farms included 336 dairy cows in normal lactation period. Parameters observed were agro-climate condition, feed consumption, milk production and milk quality, and sub-clinical mastitis prevalence. Result sowed that THI at <1000 m asl had a range of 76.1-76.7 leads to mild heat stress, while THI at ≥1000 m asl had a range of 66.2 - 66.8 which makes comfort environment to the dairy cow. Differences in feed consumption (P<0.01), milk production and quality (P<0.05) were found among two altitude study location. Milk production at ≥1000 m asl was 2.3 kg higher than at <1000 m asl. The udder health status was also different, a 51% of total sample at <1000 masl was detected sub-clinical mastitis (SCM) as high criteria, while 42% samples that were collected at ≥1000 m asl detected sub-clinical mastitis as middle criteria. In conclusion, agro-climate condition (THI) affect animal’s comfort, milk production and sub-clinical mastitis prevalence.